Portal vein thrombosis after cetuximab and 5-fluorouracil therapy in a patient with advanced colon cancer and decompensated cirrhosis: a case report and review of the literature - Fangyu Liu; Yongmei Xu; Guowang Yang; Yuhong Guo; Jiayun Nian (World Journal of Surgical Oncology, 2023)
Abstract Background Treatment options for advanced colon cancer are mainly combinations of chemotherapy and targeted drugs. However, poor physical health and medication intolerance limit the choice of anticancer drugs. Colon cancer with cirrhosis is a particular patient group that poses a challenge to clinical treatment. Case presentation This article presents a case of a patient in the decompensated stage of cirrhosis who was diagnosed with advanced colon cancer. The initial presentation was a nodule on his navel named the Sister Mary Joseph’s nodule, which was later confirmed by biopsy and PET-CT as one of the metastases of colon cancer. The patient was treated with cetuximab and 5-fluorouracil at a below-guideline dose; however, portal vein thrombosis developed and led to death. This entire process, from diagnosis to death, occurred within a span of three months. Conclusion Cancers with cirrhosis are a special group that deserves more attention. There is no unified treatment guideline for these patients, especially those with extrahepatic primary tumors. We should be more cautious when choosing treatment for such patients in the future. Both chemotherapy and targeted treatment may potentially induce portal vein thrombosis, which appears to have a higher incidence and worse prognosis than cancers without cirrhosis.